Strategi Cyber PR Membentuk Persepsi Masyarakat Terkait Reputasi Sosial Instagram PKS - Khofifah Hana Nabilla; Lathifa Prima Ghanistyana; Nasywa Amalia Putri; Nazwa Fitri Setiawan; Selamitha Hayari (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
The Erspo brand as the new apparel of the Indonesian National Football Team reaped a lot of controversy after releasing the national team’s latest jersey. Football supporters think the jersey design by erspo is far from expectations. Not a few supporters opposed to raising the hashtag #boikoterspo on social media. Criticism and disappointment that was thrown made erspo in a crisis situation. The aim of this study is to analyze how crisis communication is carried out by Erspo in an effort to handle the crisis. A qualitative approach was taken with a case study research method using Situational Crisis Communication Theory (SCCT). This research uses secondary data collection methods obtained through document analysis, literature review and relatvant sources. The data analysis technique is deductive which is carried out as the data collection process is carried out. This research show that Erspo is included in the preventable cluster. The crisis response strategy implemented by Erspo is Rebuild, Erspo also implements other crisis response strategies by changing its logo design. To ensure that the data can be said to be valid and accurate, data triangulation is carried out to obtain data that can be accounted for. This research will provide novelty in analyzing crisis communication towards efforts to handle a brand experiencing a crisis.